Program Kebijakan Pengembangan Lanskap Wisata Daya Tarik Wisata Pantai Melasti, Desa Ungasan, Kecamatan Kuta Selatan, Badung - Pawitra, Luh Putu Yulia Pradnya; Yusiana, Lury Sevita; Pradnyawathi, Ni Luh Made (Jurnal Arsitektur Lansekap, 2023)
Tourism Landscape Development Policy Program Melasti Beach Tourist Attraction, Ungasan Village, South Kuta District, Badung. Melasti Beach is located in Badung Regency, this natural tourist attraction is used for tourist activities and socio-religious activities. The tourism activity in Melasti Beach requires the landscape development must takes into account the supporting tourism aspects and the socio-religious aspects in it. The purpose of this research is to create a policy program for developing the Melasti Beach tourism landscape that is harmonious between the supporting tourism aspects and socio-religious aspects. The method used is a survey with data collection techniques through observation, interviews and literature study. The stages in this research consist of preparation, data inventory, data analysis, data synthesis and making tourism landscape development policy programs. Analysis and data synthesis were carried out quantitatively using level of assessment and descriptive levels to obtain a reference for making tourism landscape development policy programs that refer to the Tri Mandala concept. The planned policy program are planned in the form of space management programs, recommendations for problem solving and circulation during religious ceremonies and other tourist activities.